2022
DOI: 10.3389/fgene.2022.988047
|View full text |Cite
|
Sign up to set email alerts
|

Integrative analyses of potential biomarkers and pathways for non-obstructive azoospermia

Abstract: Background: Non-obstructive azoospermia (NOA) is the most severe form of male infertility. Currently, the molecular mechanisms underlying NOA pathology have not yet been elucidated. Hence, elucidation of the mechanisms of NOA and exploration of potential biomarkers are essential for accurate diagnosis and treatment of this disease. In the present study, we aimed to screen for biomarkers and pathways involved in NOA and reveal their potential molecular mechanisms using integrated bioinformatics.Methods: We down… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…In addition, Zhong et al. ( 53 ) indicated that CD8+ T cell was dominantly enriched in immune infiltration of patients with non-obstructive azoospermia. Cytokines generated from monocytes and macrophages were detected in human semen.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, Zhong et al. ( 53 ) indicated that CD8+ T cell was dominantly enriched in immune infiltration of patients with non-obstructive azoospermia. Cytokines generated from monocytes and macrophages were detected in human semen.…”
Section: Discussionmentioning
confidence: 99%
“…Mylvaganam et al (52) showed that high levels of monocyte/ macrophage and cytokines in acute COVID-19, persistently resulting in the activation of fibroblastic signaling and further leading to pulmonary fibrosis. In addition, Zhong et al (53) indicated that CD8+ T cell was dominantly enriched in immune infiltration of patients with non-obstructive azoospermia. Cytokines generated from monocytes and macrophages were detected in human semen.…”
Section: Discussionmentioning
confidence: 99%
“…The construction of a disease-associated competitive endogenous RNA regulatory network could help to analyse the biological mechanisms of key genes in disease regulation. And most of them lacked the analysis of immune infiltration, where the immune system plays an important role in spermatogenesis ( 10 ). These omissions set the stage for the present study.…”
Section: Introductionmentioning
confidence: 99%